The Reality of Using Artificial Intelligence Applications in Scientific Research from the Point of View of Faculty Members at the University of Ha’il - Almansour, Dr. Shahad Mousa; Samil, Dr. Samia Ahmed; Elshnawe, Amal Abdelkader; Maali, Sana Mahmood; Mustafa, Dr. Jehan Hazim Habib (Journal of Ecohumanism, 2025)
The current study aimed to identify the reality of using artificial intelligence applications in scientific research from the point of view of faculty members at the University of Ha’il. The descriptive survey method was used, through a questionnaire consisting of (30) items, and the validity and reliability of the tool was confirmed. The sample consisted of (243) faculty members at the University of Ha’il who were selected by a simple random method. After collecting and processing the data. The results showed a high degree of use of artificial intelligence in scientific research, and there are no statistically significant differences due to the faculty members variables of gender, experience, and academic rank. In light of these results, the researchers recommended the use of artificial intelligence applications in scientific research without compromising the ethics of scientific research.